Crude oil price shocks, monetary policy, and China's economy. (11th October 2018) - Wen, Fenghua; Min, Feng; Zhang, Yue‐Jun; Yang, Can
Abstract: This paper develops a time‐varying parameter vector autoregressive model to examine the dynamic effects of crude oil prices and monetary policy on China's economy during January 1996 to June 2017. The empirical results indicate that (a) in general, international crude oil price shocks have positive effect on China's economic growth and inflation in the short run, but the long‐run effect appears diverse; (b) China's monetary policy shocks have positive effect on the economic growth and inflation overall; specifically, an increase in monetary supply can partly offset crude oil prices' negative effect on China's economic growth; (c) China's monetary policy has positive effect on crude oil prices and plays an important role in the relationship between crude oil price shocks and economy; and (d) during the recent global financial crisis, crude oil price shocks produce greater negative effect on China's economic growth, whereas the long‐run effect of monetary policy on China's economic growth proves weaker, compared with other periods.